القيصرية الحديثة أم القيصرية الكلاسيكية - ديوب, ميسون (Latakia University Journal -Medical Sciences Series, 2019)
This study was conducted at Tishreen Hospital University in Lattakia in the department of obstetrics and gynecology between 1/1/2016 -1/1/2017 The study sample consisted of 270 caesarean sections, which were administered for a patient with one caesarean section. • The first group is 78 patients wish modern caesarean section. • The second group is 192 patients with classic cesarean section. The study conducted a comparison between the two groups. The results were as follows: 1- The percentage of adhesions in the first group was 41% while in the second group 48.9% 2- We did not notice any significant difference in the thickness of LSCS between the two groups using abdominal ultrasound. § good scar which their thickness ≥ 3 mm The rate of good scars of first group were 84.6%. The rate of good scars of second group were 82.2%. 3- There were short mess of the time of caesarean about (7 – 11) minutes by the modern cesarean and short mess of the time of delivery at least 3-4 minutes. أجريت هذه الدراسة في قسم التوليد بمشفى تشرين الجامعي ما بين 1/1/2016 -1/1/2017، حيث كانت عينة الدراسة مؤلفة من 270 قيصرية أجريت لمريضه باستطباب سوابق قيصرية مع مراعاة طريقة إجراء القيصرية الأولى المجموعة الأولى 78 مريضة أجريت القيصرية الأولى بالطريقة الحديثة المجموعة الثانية 192 مريضة أجريت القيصرية الأولى بالطريقة التقليدية قامت الدراسة بإجراء مقارنة بين المجموعتين في النقاط التالية: 1- نسبة حدوث الالتصاقات بالإضافة الى شدتها وتوضعها 2- ثخانة القطعة السفلية 3- مدة إجراء القيصرية كاملة ومدة استخراج الجنين 4- لم تدرس شدة النزف في كلا الطريقتين لأنها مقدرة عالميا ب 1000 مل في القيصرية بشكل وسطي بغض النظر عن الطريقة وهي تعود في معظمها لانفكاك المشيمة ولصعوبة تقدير الكمية الناجمة عن الجراحة بشكل معزول فكانت النتائج على الشكل الآتي: 1- بلغت نسبة الالتصاقات بالفئة الأولى 41% وبلغت في الفئة الثانية 48,9% 2- لم نلاحظ اختلافا ذو أهمية فيما يتعلق بالثخانة بالنسبة للقطعة السفلية للرحم بين المجموعتين وذلك باستخدام الايكو البطني الندب الجيدة بالفئة الأولى 84,6% ( ندبة جيدة ≥ 3 ملم ) الندب الجيدة بالفئة الثانية 82,2% 3- وجد اختصار هام لزمن القيصرية يبلغ وسطيا 7-11 دقيقة في الطريقة الحديثة إضافة لاختصار زمن ولادة الجنين بما لا يقل عن 3-4 دقائق